The psychosocial risk factors of internet gaming disorder among Malaysian young adult players - Nur Laila Azzwa Nordin; Nor Ba'yah Abdul Kadir; Rusyda Helma Mohd; Mohd Rizal Abdul Manaf; Normaliza Ab Malik; Mark D Griffiths (Arts and Science Press Pte. Ltd., 2026)
Indexed by SCOPUS